Il lavoro della ragione Dimensioni del soggetto nella Fenomenologia dello spirito di Hegel - Roni, Riccardo (Strumenti per la didattica e la ricerca, 2012)
In our age now deprived of the traditional metaphysical certainties, to study the moral dimension of subjectivity in Hegel's The Phenomenology of Spirit is to make one's object of investigation that which is one of the themes of greatest philosophical interest, precisely owing to its great topicality. Hegel deals with the moral issue in a particularly profound manner, aware both of the contradictory and dramatic aspects of that experience and of the centrality of the motif of the «beyond». On the basis of this interpretative thesis, the analyses of Hegel's text made in this research are devoted to focussing on the experiences of the subject's constitution and legitimization together with the unexpected consequences deriving from the problematic relationship that the consciousness establishes with the self-sufficient immobility of substance. The result is a historiographical and theoretical study that slots effectively into the contemporary debate on the great topicality of Hegel's thought.